Free Trade versus Protection : Static and Dynamic Aspects (The Pakistan Development Review, 1985)
This paper analyses whether the developing countries are pursuing an optimal foreign trade policy, given the theoretical and empirical evidence we have. The paper concludes that constraints in imposing other taxes than tariffs in many developing countries may justify having tariffs as part of an optimal taxation policy.